PREVALENCE AND SEVERITY PATTERNS OF ALCOHOLIC LIVER DISEASE AT A TERTIARY HOSPITAL IN BENIN CITY, NIGERIA - Adeogun, Esther F.; Mokwenye, Victoria N.; Iyayi, Theophilus (FUDMA Journal of Sciences, 2026)
The ratio of Aspartate aminotransferase (AST) and Alanine aminotransferase (ALT) (De Ritis ratio) remains a vital biochemical marker in hepatology. Although both AST and ALT are indices of liver injury, the ratio of these two enzymes helps clarify the etiology and severity of liver disease. A retrospective analysis was conducted on 7,580 liver function test (LFT) requests received from May 2024 to May 2025 at the University of Benin Teaching Hospital (UBTH), Benin City, Nigeria. UBTH is a tertiary health facility with over 900 bed capacity, serving treatment, teaching, health, research and referral purposes for Edo State with its adjoining states. Of the 7,580 requests received, 284 (3.7%) cases demonstrated elevated levels of De Ritis Ratios (AST:ALT) greater than 2:1 indicating Alcoholic Liver Disease (ALD). These cases were further examined based on their gender, ethnicity and age. There was a marked male predominance (67.3%) compared to females (32.7%). The distribution across ethnic groups highlighted significant regional variability in which Delta (40%) was the highest, followed by Bini (24%), Ibo (15%), Yoruba (15%) and Hausa (6%).  Age range of 40 to 49 (21.5%) had the highest number of De Ritis ratio. There was a higher prevalence of suspected ALD in males and a significant age-related distribution based on De ritis ratio values. The prevalence of liver disease is low (3.7%) in the population that accessed the health care facility within the period studied.
Keywords: Liver Function Test; ALD; De-Ritis Ratio; AST; ALT; Healthcare Facility